Upaya Meningkatkan Kompetensi Guru Sasaran dalam Proses Pembelajaran Melalui Supervisi Akademik di SMPN 4 Praya - Kadri, Kadri (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This research aimed to know effectiveness of implementing academic supervisor in improving teachers’ competence in learning at class, which has benefit for head master to know teachers’ improvement in learning process.this research was conducted in two cycles, every cycle has four steps namely planning, acting, observing, and reflecting. Indicator of completeness in this research was; 1) the result of headmasters’ observation and teachers’ observation as long as guiding had gotten mean score > 4,0, 2) result teachers’ mean score in learning process was > 85% with mean score was 70,00 (good category). The result in cycle I mean score of headmasters’ observation (3,80), mean score of teachers’ observation (3,00) and result of academic supervisor in target has mean score (66,12). In cycle II mean score of headmasters’ observation (4,40) with percentage of completeness (100%), mean score of teachers’ observation was (4,25) with percentage of completeness (100%) and mean score of academic supervisor was (84,92) with percentage of completeness (100%). Indicator of completeness was reached, this research was succees and stopped in cycle II. Conclusion; the result of this research in cycle II showed improvement of target teachers’ competence in learning process at real classroom. Suggestion for headmaster in order to conduct similar research in effort to improve teachers’ competence, and for teachers in similar subject in order to conduct teaching process based plan which has been arranged well, responsiple, commitment for improving students’ achievement based on subject that became their responsible.